Reality Stems From Modality: Stereotype Threat Effects of a STEM Game in Augmented and Virtual Reality - Ratan, Rabindra; Boumis, Josephine K.; Kuang, Sarah; Gambino, Andrew; Huang, Kuo-Ting (Frontiers in Virtual Reality, 2021)
This study examined the relationship between stereotype threat, game modality (augmented reality, virtual reality), and stereotypic beliefs about STEM fields. Results of a 2 [modality] x 2 [stereotype threat] factorial, between-subjects experiment with women participants (N = 64) suggest that gender stereotypes primed before playing the STEM game in AR led to stereotype threat, but led to stereotype reactance in VR. Specifically, for participants who played in AR, the stereotype-reinforcing prompt (compared to a counter-stereotype prompt) led to worse STEM-game performance, which mediated an increase in stereotypical beliefs about women in STEM. Conversely, for participants who played in VR, the stereotype-reinforcing prompt led to better STEM-game performance and more positive (i.e., counter-stereotypic) beliefs about women in STEM, though without mediation. These findings support the argument that VR is more male-stereotyped than AR and that regardless of modality, stereotypes triggered in a STEM-gaming context have the potential to reinforce stereotypes in STEM fields.